Building Resilience for Transformational Recovery: An Analysis of Monetary Policy and Economic Growth in West Africa before and Following the COVID-19 Periods - Awoyemi, Bosede Olanike; Achukwu, Mark; Asala, Simon; Aiyegbusi, Oluwole; Onikate-Amosu, Tajudeen Abiodun (International Journal of Economics and Financial Issues, 2024)
This study investigates the effectiveness of monetary policy in the pre and post COVID-19 periods in West Africa. The panel fully modified ordinary least squares (FMOLS) was used. Before the estimation, the correlation analysis and summary statistics were done. Unit root test was carried out to ascertain whether the data series are stationary or not and the panel cointegration test was used to determine the existence of long run relationship among the variables. The findings indicate that monetary policy has 12.3% negative and significant effects on economic growth in the periods before COVID-19, while it has insignificant effect after the pandemic. Furthermore, monetary policy has 21.01% negative and significance effects on inflation in the pre COVID-19 era, while it has 52.5% negative and significant effect on inflation after the pandemic. This indicates that the effectiveness of the central bank’s efforts to affect and control inflation has declined after COVID-19. Causes for this could include the pandemic’s effect on supply chains, demand, and the weaker economic environment. On this basis, the monetary authority should create an economic environment that will play a crucial role in determining the effectiveness of monetary policy in the post-COVID-19 periods to foster economic recovery.